Integrating Religious Moderation Values into Islamic STEM Education: Its Impact on Students' Critical Thinking Skills and Scientific Literacy - Muksin Alatas; Prima Crismono; Achmad Faisol; Mahnawawe Yakoh (Ikatan Cendikiawan Ilmu Pendidikan Islam (ICIPI), 2026)
Although STEM education has been widely recognized as an effective approach for developing twenty-first-century competencies, its implementation in Islamic educational institutions has largely emphasized cognitive and technical skills while paying limited attention to the integration of religious moderation values. Likewise, studies on religious moderation have predominantly focused on Islamic Religious Education rather than being embedded within interdisciplinary science learning. This study therefore aimed to examine the effect of integrating religious moderation values into Islamic STEM Education on students' critical thinking skills and scientific literacy. A quantitative approach was employed using a Pretest–Posttest Control Group Design. The research sample consisted of 64 students who were assigned to an experimental group and a control group. The experimental group received Islamic STEM instruction integrating the values of religious moderation, whereas the control group received conventional instruction. Data were collected through critical thinking tests, scientific literacy tests, observation sheets, and documentation, and were analyzed using descriptive statistics, normality and homogeneity tests, and Multivariate Analysis of Variance (MANOVA). The findings revealed that the implementation of Islamic STEM Education integrated with religious moderation values had a statistically significant effect on students' critical thinking skills and scientific literacy simultaneously (p < 0.05). Students in the experimental group achieved substantially higher improvements in both critical thinking and scientific literacy than those in the control group. Classroom observations further indicated that embedding the principles of tolerance, balance, justice, and respect for diversity fostered an inclusive and collaborative learning environment that encouraged evidence-based reasoning and scientific inquiry. Conceptually, the findings demonstrate that integrating religious moderation values strengthens the effectiveness of STEM learning by connecting scientific reasoning with ethical, inclusive, and socially responsible perspectives. This integration contributes to a more holistic instructional model that promotes not only critical thinking and scientific literacy but also the development of twenty-first-century competencies and students' moderate religious character. Therefore, Islamic STEM Education integrated with religious moderation values offers an innovative framework for improving both the quality of science education and character education in Islamic schools.